(untitled) (TEST Ticontre. Theory Text Translation, 2018)
Eros and Poetry point to an integral vision of reality, so that the body of the eroticized Word appears as the extreme limit of knowledge. In Lezama Lima’s writing, the incorporation of the erotic, of the non separate, makes sensitive experience become a sign of identity and permanence. For the Cuban writer, the erotic saying is always linked to the origins of creation, to the previous fullness of a world that still needs to be done. Eros y poesía apuntan a una visión íntegra de la realidad, de modo que el cuerpo de la palabra erotizada aparece como el límite extremo del conocimiento. En la escritura de Lezama Lima, la incorporación de lo erótico, de lo no separado, hace que la experiencia sensible se convierta en signo de identidad y permanencia. Para el escritor cubano, el decir erótico siempre va ligado a los orígenes de la creación, a la plenitud anterior de un mundo que todavía está por hacer.